A REGIONAL MODEL TO TEST THE CONCEPT OF GLOBAL EASTWARD MANTLE FLOW USING FINITE ELEMENTS - (:unkn) unknown (My University, 2009)
Computer modeling of tectonics involving the entire Caribbean and North Andes plates, as well as most of the Cocos plate and a portion of the Nazca plate, have been used to support the concept of a global eastward mantle flow beneath the region. The eastward flow is interpreted to be the results of a lithospheric rotation relative to the asthenosphere. The tectonic modeling has been used in combination with observations for the region to support a best fitting model that includes the global eastward flow.

The best fitting model to surface observations used parameters consisting of a due east asthenosphere flow at 100 mm/yr, a base of lithosphere temperature of 1380 K, and a fault friction coefficient of 0.12. The results from the best model demonstrate that a simple uniform eastward flow in the asthenosphere can account for the varying directions of movement and velocities on the surface for the tectonic plates in this region. The model was able to reproduce the simultaneous movements for the Caribbean plate, at nearly due east, the North Andes plate to the northeast, the Nazca plate due east, and the Cocos plate to the northeast. In addition, the best model was able to reproduce the large velocity contrasts between the Cocos plate at 70 plus mm/yr relative to the Caribbean plate at 20 mm/yr and the velocity contrast between the Nazca plate at 50 plus mm/yr and the North Andes plate at 10 mm/yr. These results demonstrate that simple uniform flow of the asthenosphere to the east in conjunction with plate to plate interaction can explain the complex movements that we observe for the tectonics of this region, and might serve as an overall global model.
Keywords: Plate tectonics; Earth (Planet)--Mantle; Geophysics; Geodynamics